Transcriptome analysis of high- and low-selenium genotypes identifies genes responsible for selenium absorption, translocation, and accumulation - Li, Ling; Ahsan, Muhammad Zahir; Li, Zhe; Panhwar, Faiz Hussain; Zhang, Yue; Luo, Dan; Su, Yang; Jia, Xiaomei; Ye, Xiaoying; Shen, Caihong; Wang, Songtao; Zhu, Jianqing (Frontiers in Plant Science, 2024)
Introduction Selenium is an essential micronutrient the human body requires, which is closely linked to health. Rice, a primary staple food globally, is a major source of human selenium intake. To develop selenium-enriched rice varieties, it is imperative to understand the mechanisms behind selenium’s absorption and transport within rice, alongside identifying the key genes involved in selenium uptake, transport, and transformation within the plant. Methods This study conducted transcriptome sequencing on four types of rice materials (two with low-selenium and two with high-selenium contents) across roots, stems, leaves, and panicles to analyze the gene expression differences. Results and discussion Differential gene expression was observed in the various tissues, identifying 5,815, 6,169, 7,609, and 10,223 distinct genes in roots, stems, leaves, and panicles, respectively. To delve into these differentially expressed genes and identify the hub genes linked to selenium contents, weighted gene co-expression network analysis (WGCNA) was performed. Ultimately, 10, 8, 7, and 6 hub genes in the roots, stems, leaves, and panicles, respectively, were identified. The identification of these hub genes substantially aids in advancing our understanding of the molecular mechanisms involved in selenium absorption and transport during the growth of rice.